Sea change - Parker, Robert B., 1932- (New York : G.P. Putnam's Sons, 2005)
Jesse Stone investigates the murder of a woman, who is found in a cove near Paradise, Massachusetts. This leads to a world of wealth and depravity centered on a couple of yacht owners from Florida and their crowd.
Keywords: Stone, Jesse (Fictitious character) -- Fiction; Police -- Massachusetts -- Fiction; Police chiefs -- Fiction; Massachusetts -- Fiction; Mystery fiction